Comparison of explicit values clarification method (VCM), implicit VCM and no VCM decision aids for men considering prostate cancer screening: protocol of a randomized trial - S. Baptista; B. Heleno; A. Teixeira; K. L. Taylor; C. Martins (BMC Medical Informatics and Decision Making, 2020)
Abstract Background Screening with prostate-specific antigen (PSA) test for prostate cancer is considered a preference sensitive decision; meaning it does not only depend on what is best from a medical point of view, but also from a patient value standpoint. Decision aids are evidence-based tools which are shown to help people feel clearer about their values; therefore it has been advocated that decision aids should contain a specific values clarification method (VCM). VCMs may be either implicit or explicit, but the evidence concerning the best method is scarce. We aim to compare the perceived clarity of personal values in men considering PSA screening using decision aids with no VCM versus an implicit VCM versus an explicit VCM. Methods Male factory employees from an industrial facility in the Northern region of Portugal aged 50 to 69 years old will be randomly assigned to one of three decision aid groups used to support prostate cancer screening decisions: (i) decision aid with information only (control), (ii) decision aid with information plus an implicit VCM, (iii) decision aid with information plus an explicit VCM. Men will be allowed release time from work to attend a session at their workplace. After a brief oral presentation, those willing to participate in the study will fill the baseline questionnaire, plus a 5 point-Likert scale question about intentions to undergo screening, and will then receive the intervention materials to complete. We estimated a total sample size of 276 participants; with 92 in each group. The primary outcome will be the perceived clarity of personal values assessed by the Portuguese validated translation of the three subscales of the Decisional Conflict Scale. Secondary outcomes will be intention to be screened (before and after the intervention), the total score from the Decisional Conflict Scale and the self-report of having or not undergone screening at 6 months. Discussion This study will add to the body of evidence on the role of decision aids to support health preference-sensitive choices and provide further insight on the impact of different methods for eliciting people’s values embedded within a decision aid. Trial registration NCT03988673 - clinicalTrials.gov (2019/06/17).